Trade and Economic Cooperation of the EAEU countries with the Republic of Tajikistan - Z. A. Dadabaeva (Проблемы постсоветского пространства)
Recent years have become a time for the Eurasian space to rethink integration priorities. The existing associations in the post-Soviet space were not able to fully cover the entire range of interests of countries and not all countries were ready for even closer integration. An important task of forming and strengthening of the EAEU, the most successful integration is to create «outer contour» of the Eurasian integration and the development of bilateral relations with third countries, including developing a system of trade-economic relations with partners outside the EAEU. In this regard, considering the prospects of cooperation between the EAEU and border States, on the example of Tajikistan, is an urgent and timely task.The Republic occupies a special place in integration projects in the post-Soviet space and is located on the periphery of the CIS. But, having difficult geographical and natural conditions, and possessing considerable geopolitical, economic, demographic potential, the country has no real opportunities for their use.Awareness of the importance and necessity of integration with stronger and economically developed States is justified by the fact that the Republic, like other countries in the region, is in the zone of political, economic and military interests of the largest world powers (Russia, the United States, Europe, China, India).The analysis of Tajikistan’s bilateral economic relations with each of the EAEU countries shows, that only Russia and Kazakhstan have stable trade and investment ties with it. In this regard, the factor of the EAEU is not yet decisive in the foreign economic priorities of Tajikistan, which is highly dependent on other international partners, primarily China. But the search for new formats of interaction in the Eurasian space can provide the Republic with a stable economic situation.